Reiterative infusions of MSCs improve pediatric osteogenesis imperfecta eliciting a pro‐osteogenic paracrine response: TERCELOI clinical trial. Issue 1 (13th January 2021) - Infante, Arantza; Gener, Blanca; Vázquez, Miguel; Olivares, Nerea; Arrieta, Arantza; Grau, Gema; Llano, Isabel; Madero, Luis; Bueno, Ana Maria; Sagastizabal, Belén; Gerovska, Daniela; Araúzo‐Bravo, Marcos J; et al.
Abstract: Background: Osteogenesis imperfecta (OI) is a rare genetic disease characterized by bone fragility, with a wide range in the severity of clinical manifestations. The majority of cases are due to mutations in the COL1A1 or COL1A2 genes, which encode type I collagen. Mesenchymal stem cells (MSCs), as the progenitors of the osteoblasts, the main type I collagen secreting cell type in the bone, have been proposed and tested as an innovative therapy for OI with promising but transient outcomes. Methods: To overcome the short‐term effect of MSCs therapy, we performed a phase I clinical trial based on reiterative infusions of histocompatible MSCs, administered in a 2.5‐year period, in two pediatric patients affected by severe and moderate OI. The aim of this study was to assess the safety and effectiveness of this cell therapy in nonimmunosuppressed OI patients. The host response to MSCs was studied by analyzing the sera from OI patients, collected before, during, and after the cell therapy. Results: We first demonstrated that the sequential administration of MSCs was safe and improved the bone parameters and quality of life of OI patients along the cell treatment plus 2‐year follow‐up period. Moreover, the study of the mechanism of action indicated that MSCs therapy elicited a pro‐osteogenic paracrine response in patients, especially noticeable in the patient affected by severe OI. Conclusions: Our results demonstrate the feasibility and potential of reiterative MSCs infusion for two pediatric OI and highlight the paracrine response shown by patients as a consequence of MSCs treatment. Abstract : TERCELOI clinical trial addresses fundamental issues concerning the feasibility, security and potential of 5 MSCs infusions in two non immunosuppressed Osteogenesis Imperfecta pediatric patients. This trial allowed us to elucidate the mechanism of action of MSCs therapy, characterized by a pro‐osteogenic paracrine response. For that, we studied the protein and miRNA levels in sera from patients (collected before, along and after the cell treatment) besides unraveling the transcriptomic alterations due to those sera presence, and demonstrating their functional capabilities.